Review of Reconstructions: The Troubles in Photographs and Words by Steafán Hanvey and Bobby Hanvey - Noémie Beck (Review of Irish Studies in Europe)
Review of Reconstructions: The Troubles in Photographs and Words, Poems and Words by Steafán Hanvey, Photographs by Bobbie Hanvey, (Ireland: Merrion Press,2019). 155 pp. ISBN 97817853722162, €19.95.